Evaluation of in vitro and in vivo anti-inflammatory activity of biologically active phospholipids with anti-neoplastic potential in porcine model - Vicenova, Monika; Nechvatalova, Katerina; Chlebova, Katarina; Kucerova, Zdenka; Leva, Lenka; Stepanova, Hana; Faldyna, Martin (BMC complementary and alternative medicine, 2014)
BACKGROUND: This study aims to investigate the anti-inflammatory effect of biologically active phospholipids (BAP) used in preparations for clinical practice in humans. Until date, except anti-neoplastic ability, little is known about anti-inflammatory property of the phospholipids. METHODS: While the course of bacterially induced acute pneumonia and markers of inflammation were studied in in vivo system in pigs orally supplemented with BAP, the pro- and anti-inflammatory response of lipopolysaccharide-stimulated porcine monocyte-derived macrophages to 24 h- and 48 h-treatment by BAP was investigated in in vitro system. In vivo, the animal health status was monitored and pro-inflammatory IL-1β and IL-8 in sera were detected by ELISA during the experiment, while bronchoalveolar lavage fluids (BALF) and the lungs were examined post-mortem. Total and differential counts of white blood cell (WBC) were determined in blood and BALF. In vitro, mRNA expression of pro-inflammatory (TNF-α, IL-1β, CXCL10) and anti-inflammatory (IL-10 and Arg1) cytokines, and level of activated caspase 1 and phosphorylated protein kinase C epsilon (pPKCϵ), were studied using qRT-PCR and Western blot, respectively. For the purposes of both systems, 6 animals were used in each of the BAP-supplemented and the control groups. RESULTS: In vivo, BAP had a positive influence on the course of the disease. The immunomodulatory effects of BAP were confirmed by lower levels of IL-1β, IL-8, and a lower WBC count in the supplemented group in comparison with the control group. A lower percentage of lung parenchyma was affected in the supplemented group comparing to the control group (on average, 4% and 34% of tissue, respectively). In vitro, BAP suppressed mRNA expression of mRNA for IL-10 and all pro-inflammatory cytokines tested. This down-regulation was dose- and time-dependent. Arg1 mRNA expression remained unaffected. Further dose- and time-dependent suppression of the activated caspase 1 and pPKCϵ was detected in macrophages when treated with BAP. CONCLUSIONS: Our results demonstrate that BAP has anti-inflammatory and immunomodulatory properties, thus emphasizing the potential of this compound as a natural healing agent.
Keywords: Leukocytes; plíce; makrofágy; Pneumonia, Bacterial; Animals; kultivované buňky; lipopolysacharidy; Anti-Inflammatory Agents; Macrophages; antiflogistika; Swine; Cytokines; fosfolipidethery; Cells, Cultured; Phospholipid Ethers; zvířata; prasata; Inflammation; bakteriální pneumonie; cytokiny; zánět; Lipopolysaccharides; bronchoalveolární lavážní tekutina; Bronchoalveolar Lavage Fluid; Lung; leukocyty